2016
DOI: 10.1007/s11999-016-4707-5
|View full text |Cite|
|
Sign up to set email alerts
|

Reoperation After Cervical Disc Arthroplasty Versus Anterior Cervical Discectomy and Fusion: A Meta-analysis

Abstract: Background Anterior cervical discectomy and fusion is a standard surgical treatment for cervical radiculopathy and myelopathy, but reoperations sometimes are performed to treat complications of fusion such as pseudarthrosis and adjacent-segment degeneration. A cervical disc arthroplasty is designed to preserve motion and avoid the shortcomings of fusion. Available evidence suggests that a cervical disc arthroplasty can provide pain relief and functional improvements similar or superior to an anterior cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 47 publications
2
41
0
4
Order By: Relevance
“…Decades of technological advancements have lead to the current devices available to spine surgeons, some of which have produced excellent mid-term results [11][12]13••, [14][15]. Cadaveric studies have supported these findings from a biomechanical standpoint, and several investigations have shown superior patient outcomes, higher patient satisfaction, less implant related complications, and lower reoperation rates in comparing CDR with ACDF [8,14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Decades of technological advancements have lead to the current devices available to spine surgeons, some of which have produced excellent mid-term results [11][12]13••, [14][15]. Cadaveric studies have supported these findings from a biomechanical standpoint, and several investigations have shown superior patient outcomes, higher patient satisfaction, less implant related complications, and lower reoperation rates in comparing CDR with ACDF [8,14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…IDE studies have suggested that ACDA may be effective in achieving this goal, with fewer subsequent surgeries performed in patients treated with ACDA versus ACDF. [10,18,19,11] However, these results have not been consistent across the literature, which raises concern for bias arising from the industry-sponsored investigations and the generalizability of the results from these studies. [6,20,14] Furthermore, the introduction of new technologies is necessarily associated with a learning curve and, as such, perioperative complications may be more common as the technology is adopted.…”
Section: Discussionmentioning
confidence: 82%
“…There are several studies that have demonstrated a publication bias in the cervical disc replacement literature [32,33]. Therefore, systematic reviews of cervical disc replacement literature are challenging to interpret because there are likely studies with equivalent or negative results that have not been reported and not included in these reviews.…”
Section: Publication Biasmentioning
confidence: 99%